Mentoring, not Monitoring: Mediating a Whole-School Model in Supervising Preservice Teachers - Sanford, Kathy; Hopper, Tim (Alberta Journal of Educational Research, 2000)
This article offers a case study of a whole-school model for supervising preservice teachers that is related to the principles of professional development schools (Holmes Group, 1990) and Zeichner's (1992) notions of rethinking student teachers' practicum experience. The article draws on constructivist notions of learning to teach; in particular, reference is made to Vygotsky's (1978) sense of mediating a stimulus where in a social-cultural context a person's knowledge is created, examined, and transformed rather than simply absorbed and transmitted. The case study highlights the particular details of this whole-school model and connects these to five main empirical descriptors that were generated from data triangulated from preservice teachers' journals, evaluation forms, group meetings, and correspondence from cooperating teachers. The descriptors show how the whole-school model evolved and how the role of university facilitator shifted from monitoring to mentoring in the teacher preparation process. This change in relationship disrupted the isolating clinical model of supervision where the university facilitator and cooperating teacher, in an uneasy relationship, are perceived by preservice teachers as having power over them: "telling" the preservice teacher with little perceived opportunity for negotiation.